Poetry and Philosophy in the Sophists - Allan, William (Araucaria, 2020)
This paper examines the relationship between poetry and philosophy in the sophists, asking what role earlier traditions of poetry and song played in their work. The sophists’ influence on various genres of literature and philosophy is widely acknowledged, but, as this paper shows, the influence of earlier traditions of poetry and myth on their work was no less important. The paper demonstrates too how the sophists’ engagement with the poetic tradition, like that of the Presocratics, was geared primarily to serve their philosophical or didactic goals, even if the aesthetic benefits of poetic language and style were also appreciated and exploited. Moreover, the sophists recognized poetry’s important role in education, and their varied use of poetic language, style, and content in their own teaching was a continuation of this traditional aspect of poetry. In conclusion, the sophists’ work on rhetorical, political, and ethical issues engaged with, and was enriched by, the shared poetic culture of their time.